2018
DOI: 10.1016/j.techfore.2018.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Did the global financial crisis impact firms' innovation performance? The role of internal and external knowledge capabilities in high and low tech industries

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
124
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(127 citation statements)
references
References 99 publications
1
124
0
2
Order By: Relevance
“…However, evidence show that firms are able to cope better during recession periods by having invested in R&D activities (Zouaghi et al 2018). Archibugi et al 2013, in their analysis of three waves of the UK Community Innovation Survey (CIS), find that the lack of internal financial resources hampered innovation during the economic crisis;…”
Section: Moderating Effects Of the Financial Crisismentioning
confidence: 99%
See 1 more Smart Citation
“…However, evidence show that firms are able to cope better during recession periods by having invested in R&D activities (Zouaghi et al 2018). Archibugi et al 2013, in their analysis of three waves of the UK Community Innovation Survey (CIS), find that the lack of internal financial resources hampered innovation during the economic crisis;…”
Section: Moderating Effects Of the Financial Crisismentioning
confidence: 99%
“…Second, the paper examines how dynamic capabilities enable firms to avoid the risk of failure during economic downturns. These capabilities encompass activities through which managers continuously configure assets into viable resource combinations (Fainshmidt et al, 2017), and are likely to influence the incidence of business failure during the global financial crisis (Ahn et al 2018;Zouaghi et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Previous works in this field support this theoretical vision, showing, for example, that low-tech sectors do not lack opportunities for innovation, but these opportunities often take a different form than those in the hightech sectors (Haudeville & Bas, 2016). Moreover, highand low-tech industries require different types of innovation resources (Zouaghi et al, 2018 (Kirner et al, 2009). Research by Reichert and colleagues (2016) highlights that innovation occurs and is important not only for industries active at the technological frontier, but also for low-technology industries.…”
Section: An Randd-oriented Point Of View Challenged By the Schumpetermentioning
confidence: 84%
“…Additionally, Ramcharan et al [32] underlined that financial crises have a negative effect on consumer credit supply. Additionally, Zouaghi et al [33] identified that financial crises decrease the innovation performance of the companies. Similarly, Malik and Ghosh [34] emphasized that the financial crisis has a negative influence on the economic growth of countries.…”
Section: A Literature Review Of Global Risks and Financial Crisesmentioning
confidence: 99%